Building an Entrepreneurial Mindset For Farmers in Melo Village-Liang Ndara Mbeliling District-West Manggarai - Lena Ellitan, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Agriculture is one of the sectors that makes a big contribution to the economy in Melo village, Liang Ndara, West Manggarai Regency. This contribution certainly has a very important role for the economy in the region. Agricultural development should continue to be pursued so that its important role in the economy is maintained. However, complex farmer problems will have a negative impact on the slow development of the agricultural sector. Farmers have not been able to support tourism development in Labuan Bajo. It cannot be denied that the pattern of agricultural development in general is still production-oriented in order to achieve independent food security. Business-oriented agricultural programs are still being implemented partially by several agencies. Farmers also still lack the spirit and entrepreneurship and always have difficulty managing and developing business diversification in a productive manner amidst the abundant potential of local resources around their residential environment. Entrepreneurship has an important function as a driving force for farmers in developing various types of agricultural businesses in a productive and creative manner.